PROSES PENYELESAIAN SENGKETA PERDATA DI PENGADILAN NEGERI DALAM KAITANNYA DENGAN TRANSAKSI YANG MENGGUNAKAN INTERNET - Sanyoto, Sanyoto; Maryono, Antonius Sidik; Bintoro, Rahadi Wasi (Faculty of Law, Universitas Jenderal Soedirman, 2008)
The growth of technological Progress make the change of pattern in the socialize human life, and it can conduct the economic activity in the local scale, regional and also global. In the individual assocciation by using internet technology will take the relation pattern between individual which it is unlike what that happened in the real world. By the existence of internet, contractual terms between subject of law and each other without meeting (face to face), even it is enabled for subject of law not to recognizing each other. During the people conducting activity in the illusory world, especially in the private law, like commerce, agreement and also banking activity, it is enabled to take a problems such as performed in the conventional private relationship. If the consumer internet in the private activity feel their private rights are impinged and they are wish to claim their rights, so there is civil conflict. The relationship between the individual in the transaction using internet not yet arrange peculiarly in law and regulation. But judge have to find the law and also create the law if he confronted with a dispute in the transaction using internet. Kata kunci : hakim, hukum, internet, perdagangan elektronik, tanda tangan digital